Which preferences associate with school performance? Lessons from a university classroom experiment - Dániel Horn; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
We attempt to link laboratory-based measures of preferences with measures of school performance. We measure in an incentivized way risk, time, social and competitive preferences and also cognitive abilities of university students and look for associations between these measures and two important academic outcome measures: exam results and GPA. We find consistently that cognitive abilities (proxied by the Cognitive Reflection Test (Frederick 2005)) are very well correlated with school performance. Regarding non-cognitive skills, we find suggestive evidence for many of our measured preferences. We use two alternative measures of time preference: patience and present bias. Present bias explains exam grades relatively better, while patience is better explaining GPA. Both measures of time preferences have a non-linear relation to school performance. Competitiveness matters, as students, who opt for a more competitive payment scheme in our experiments have a higher average GPA and better exam grades. We observe also that risk-averse students perform a little better than risk-loving students. That makes sense in case of multiple choice exams, because risk-loving students may want to try to pass the exam less prepared, as the possibility of passing as exam just by chance is not zero. Finally, we have also detected that cooperative preferences - the amount of money offered in a public good game - associates strongly with GPA, but in a non-linear way. Students who offered around half of their possible amounts had significantly higher GPAs than those, who offered none or all their money.
Keywords: C91; D91; I20; 330; competititive preferences; experiment; non-cognitive skills; risk preferences; school performance; social preferences; time preferences